2002
DOI: 10.1002/gps.585
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of Clock Drawing Test and MMSE or Short Performance Test (SKT) in dementia screening in a memory clinic population

Abstract: The CDT in combination with the MMSE or SKT is an easily administered, non threatening and highly sensitive screening test for dementia in the setting of a memory clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
67
3
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 20 publications
14
67
3
13
Order By: Relevance
“…Although, Schramm et al (2002) found that combining CDT with MMSE improved sensitivity, Heinik, Solomesh, Bleich, and Berkman (2003) showed that the CDT plus MMSE combined improved both sensitivity and specificity compared with the CDT alone (Agrell & Dehlin, 1998). In addition, Samton et al (2005) found that MMSE performance and CDT were correlated as anticipated, but CDT was a more sensitive and consistent predictor of disposition compared to the MMSE.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although, Schramm et al (2002) found that combining CDT with MMSE improved sensitivity, Heinik, Solomesh, Bleich, and Berkman (2003) showed that the CDT plus MMSE combined improved both sensitivity and specificity compared with the CDT alone (Agrell & Dehlin, 1998). In addition, Samton et al (2005) found that MMSE performance and CDT were correlated as anticipated, but CDT was a more sensitive and consistent predictor of disposition compared to the MMSE.…”
Section: Discussionmentioning
confidence: 95%
“…Although the correlation between MMSE and CDT in the elderly has been studied in other countries (Shulman, Pushkar Gold, Cohen, & Zucchero, 1993;Schramm et al, 2002), there was no study addressing the strength of the relationship between the two tests among Iranian population of older adults. However, there was only one study which assessed reliability and validity of CDT in Iranian older population (Sadeghipour Roodsari, Akbari Kamrani, Foroughan, Mohammadi, & Karimloo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the maximum achievable score in this version of the CDT is 4 points, whereas the lowest score is 0 points. 25) Beck Depression Inventory (BDI): The BDI is a 21-item self-reporting scale developed to measure the severity of depression. The Turkish version is a reliable and valid tool that is extensively used.…”
Section: Making A-b (Tm-a-b)mentioning
confidence: 99%
“…In the BAI, the categories are normal (0-7), mild (8)(9)(10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and severe . 27) …”
Section: Beck Anxiety Inventory (Bai)mentioning
confidence: 99%
“…El MMSE es el instrumento más utilizado y validado en el mundo, pero su aplicación requiere de 20 a 30 minutos y no permite detectar demencia en estadios iniciales (12) , debido a su baja sensibilidad para objetivar déficits ejecutivos y déficits leves de memoria y lenguaje (13) . Por otro lado, CAMCOG, DRS y la evaluación neuropsicológica estándar (14) , requieren de personal altamente entrenado y equipamiento especializado.…”
Section: Introductionunclassified